2019
DOI: 10.1016/j.omtm.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hFIX Activity Achieved after Single AAV5-hFIX Treatment in Hemophilia B Patients and NHPs with Pre-existing Anti-AAV5 NABs

Abstract: Currently, individuals with pre-existing neutralizing antibodies (NABs) against adeno-associated virus (AAV) above titer of 5 are excluded from systemic AAV-based clinical trials. In this study we explored the impact of pre-existing anti-AAV5 NABs on the efficacy of AAV5-based gene therapy. AMT-060 (AAV5-human FIX) was evaluated in 10 adults with hemophilia B who tested negative for pre-existing anti-AAV5 NABs using a GFP-based assay. In this study, using a more sensitive luciferase-based assay, we show that 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 25 publications
4
98
0
Order By: Relevance
“…50 We have previously shown that no impact of anti-AAV5 NABs on liver transduction was observed for NABs titers up to 1031 in NHPs and 340 in humans. 51 In the present study, therapeutic levels of hFIX expression were achieved in presence of anti-AAV5 NABs remaining after IA at titers ranging from 2261 to 8249. However, the impact of individual complement factors as well as of IgM antibodies on the neutralization activity has been reported for viruses such as hepatitis C, vesicular stomatitis and adenovirus type 5.…”
Section: Discussionmentioning
confidence: 50%
“…50 We have previously shown that no impact of anti-AAV5 NABs on liver transduction was observed for NABs titers up to 1031 in NHPs and 340 in humans. 51 In the present study, therapeutic levels of hFIX expression were achieved in presence of anti-AAV5 NABs remaining after IA at titers ranging from 2261 to 8249. However, the impact of individual complement factors as well as of IgM antibodies on the neutralization activity has been reported for viruses such as hepatitis C, vesicular stomatitis and adenovirus type 5.…”
Section: Discussionmentioning
confidence: 50%
“…It is not clear to what extent ELISA and the NAb titer correlate. One study reported little correlation in AAV2 and AAV8 [38], while in another paper, a correlation was suggested in AAV5 with a broad range of NAb titers [39]. As only low NAb titer animals were involved in our study, it may have been difficult to observe the correlation between these parameters.…”
Section: Discussionmentioning
confidence: 69%
“…37 To date, all trials have also excluded patients with pre-existing antibodies to the AAV serotype specific to each of the investigational products; however, at least one phase 3 trial for haemophilia B [NCT03569891] has lifted that exclusion criterion due to lack of evidence for associated reduced efficacy or immune responses due to pre-existing low-titre neutralising antibodies to AAV5. 45 Exclusion of key populations such children and adolescents, women with haemophilia, 46 and those with a history of inhibitors to factor replacement is consistent across Phase 1-3 haemophilia GT trials, but a GT trial in people with haemophilia A and inhibitors has been announced. 47 If GT does become available in children and adolescents, there may be ethical questions in terms of gaining informed consent.…”
Section: Questions Regarding Trial Participationmentioning
confidence: 99%